Improved Properties of the Big Five Inventory and the Rosenberg Self-Esteem Scale in the Expanded Format Relative to the Likert Format - Zhang, Xijuan; Tse, Winnie Wing-Yee; Savalei, Victoria (Frontiers in Psychology, 2019)
Previous research by Zhang and Savalei (2015) proposed an alternative scale format to the Likert scale format: the Expanded format. Scale items in the Expanded format present both positively worded and negatively worded sentences as response options for each scale item; therefore, they were less affected by the acquiescence bias and method effects that often occur in the Likert scale items. The major goal of the current study is to further demonstrate the superiority of the Expanded format to the Likert format across different psychological scales. Specifically, we aim to replicate the findings of Zhang and Savalei and to determine whether order effect exists in the Expanded format scales. Six psychological scales were examined in the study, including the five subscales of the Big Five Inventory and the Rosenberg Self-Esteem Scale. Four versions were created for each psychological scale. One version was the original scale in the Likert format. The other three versions were in different Expanded formats that varied in the order of the response options. For each scale, the participant was randomly assigned to complete one scale version. Across the different versions of each scale, we compared the factor structures and the distributions of the response options. Our results successfully replicated the findings of Zhang and Savalei, and also showed that order effect was generally absent in the Expanded format scales. Based on these promising findings, we encourage researchers to use the Expanded format for these and other scales in their substantive research.